Constraints perceived in dairying by the farmers in city conditions (Indian Journal of Animal Production and Management, 2024)
Dairy farming is one of the most popular livestock farming practiced both in villages as well as cities.  However, constraints in city conditions are more and least studied. Hence, the present study was planned  with the aim of identifying the constraints that are faced by the dairy farmers in the city conditions. The  constraints that were perceived by the farmers in the Srinagar district included feeding issues followed by  labour, health, breeding, government apathy, market and social issues. Feeding, labour, health, breeding,  govt. apathy, market and social issues ranked 1st, 2nd, 3rd, 4th, 5th, 6th and 7th in zone 1, 1st, 2nd, 3rd, 5th, 4th,  7th and 6th in zone 2, and 1st, 3rd, 4th, 2nd, 5th, 6th and 7th in zone 3, respectively.
Keywords: City; Constraints; Dairy; Farming